2012
DOI: 10.1088/0967-3334/34/1/1
|View full text |Cite
|
Sign up to set email alerts
|

An implantable bioimpedance monitor using 2.45 GHz band for telemetry

Abstract: This paper describes a multi-frequency single-channel electrical implantable bioimpedance monitor (35 mm × 35 mm × 10 mm, weight 52 g) powered by a NiMH battery. By using the tetrapolar method and injecting 10 µA(peak), the monitor is capable of measuring at 14 different frequencies, from 100 Hz to 200 kHz. It contains a ZigBee transceiver to monitor the measurements performed, and has an embedded memory for backing up the data. RC networks and in-situ heart excised tissues were used to test the system. When m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The consumption results dramatically lower with respect to designs based on the AD5933 (current consumption 10 mA, but it also requires external [8]. This result is obtained when the device is working continuously; when the module is employed in applications which does not need continuous monitoring, the overall power consumption can be further reduced through duty-cycle control of the measurements in a way similar to [11]. Furthermore, this result was obtained with a discrete components design.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The consumption results dramatically lower with respect to designs based on the AD5933 (current consumption 10 mA, but it also requires external [8]. This result is obtained when the device is working continuously; when the module is employed in applications which does not need continuous monitoring, the overall power consumption can be further reduced through duty-cycle control of the measurements in a way similar to [11]. Furthermore, this result was obtained with a discrete components design.…”
Section: Discussionmentioning
confidence: 89%
“…This causes an increase in power consumption, cost and complexity. A reduction of power consumption was obtained reducing the duty-cycle [11] of the measurements, or through application specific integrated circuit (ASIC) design [12]. The first approach is not compliant with scenarios requiring a continuous monitoring of the signal, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The popular ADCs developed for the implementation of biomedical applications are in the form of SAR ADCs, because of low small area, medium resolution and low power characteristics that are mostly attractive for the implementation of bio-sensing applications. Another form of bio-signal monitoring, idea bio-impedance measurement has recently gained interest in medical science because there are many possibilities for health tracking [17], [18]. Studies using bio-impedance have been reported for example to track breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The first issue is the low efficiency of the power transmission system and the limited power supply for an implanted device. Most implanted wireless devices are powered via either an inductive link or a non-rechargeable battery [ 6 , 9 , 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. However, each system has its disadvantages: the former, a battery-free inductive link, requires very close distance between the implanted device and the external powering module, which restricts the movement of the subject wearing the device while providing low efficiency wireless power transmission; the latter, a non-rechargeable battery having its own life span, demands inevitable surgeries to replace an exhausted battery due to the limited life span.…”
Section: Introductionmentioning
confidence: 99%